Morphology of the tongue and characteristics of lingual papillae in Cuniculus paca (Rodentia: Cuniculidae) - André Luiz Quagliatto Santos; Rogério Rodrigues de Souza; Márcia Rita Fernandes Machado; Mariana Oliveira Lima; Lorena Tannús Menezes; Lucélia Gonçalves Vieira; Priscilla Rosa Queiroz Ribeiro; Mariana Casteleti Beraldo-Massoli (Biotemas, 2013)
This paper describes the morphology of the tongue, its extrinsic muscles, and the characteristics of lingual papillae in Cuniculus paca. We used fifteen specimens from the Wild Animals Sector of Universidade Estadual Paulista (UNESP). In this species, the tongue is divided into three regions: root, body, and apex. The latter is delimited by the lingual frenum, which has the aspect of fibrous membrane. We also identified a median groove and a prominence on its dorsal surface. The extrinsic tongue muscles are the styloglossus, hyoglossus, genioglossus, geniohyoid, and milohyoid, the latter two are inserted into the hyoid apparatus. As for the presence of lingual papillae, we observed five papillae types in all specimens: filiform, fungiform, vallate, foliate, and conic. The filiform papillae are distributed throughout the apex surface and tongue body. They are caudally inclined throughout the body, until they are modified in the root region and form the conic papillae. The fungiform papillae are distributed in a large amount on the lingual apex, between the filiform papillae. This papilla type has a mushroom-like shape. Only two vallate papillae are located in the caudal portion of the lingual root, and they have an oval shape and are surrounded by a deep groove. The foliate papillae are observed in parallel grooves or slots located in the lateral portion of the tongue, between the vallate papillae and half of the intermolar prominence. In the tongue root, body, and apex we observed keratinized squamous stratified epithelium lining both the lingual papillae and the surface between them.